'Permission to be kind to myself'. The experiences of informal carers of those with a life-limiting or terminal illness of a brief self-compassion-based self-care intervention. (4th May 2022) - Diggory, Kate; Reeves, Andrew
Abstract : Background: Informal carers of someone with a life-limiting or terminal illness often experience marked levels of depression, anxiety and stress. Carers have limited free time to devote to lengthy, well-being interventions. Carers also struggle to prioritize their self-care, a factor which may help buffer some of the negative impacts of being a carer. The aim of this study was to gain insight into carers' views and perceptions of a brief, four session face to face self-compassion intervention for carers (iCare) which was created to improve well-being, increase self-compassion and develop self-care among carers. In so doing, this qualitative research addresses gaps in the literature relating to self-compassion interventions for carers and targeted self-care initiatives for carers. Method: Semi-structured interviews with nine participants of iCare were conducted and data subjected to a reflexive thematic analysis within a critical realist framework. Findings: A number of themes and sub-themes were identified. Carers discovered a kinder, less judgemental way of seeing themselves allowing themselves to recognize that they had their own individual needs. In turn this led to an intentional practise of self-care activities. Benefits from conscious self-care and self-kindness included experiencing a greater sense of calm or relaxation and the development of a more positive outlook. Conclusion: The findings highlight that a brief self-compassion intervention can have a positive impact on carers reported well-being through developing a kindlier internal orientation and locating a permission to allow themselves to practise an intentional self-care.